PREVALENSI DAN DETERMINAN ANEMIA PADA REMAJA PUTRI DI KOTA BEKASI - Raykhan Darmawan (2023)
The prevalence of anemia in female adolescents in 2018 was quite high in the age group 5-14 years of 26.8%, while in the ages of 15-24 it was 32%, this is due to the rapid growth of adolescents so that the need for iron increases. This study aims to analyze the relationship between adherence to blood supplement consumption, knowledge, attitudes, and practices related to blood supplement tablets, nutritional status, and diet with the incidence of anemia in young women at SMA Negeri Bekasi City. This research method used a cross-sectional design with a stratified random sampling technique. The required number of samples is 109 respondents. The linear regression model showed that the hemoglobin level = 10.357 + 0.018*TTD consumption + 0.015*TTD practices + 0.103*consumption of Fe sources that hemoglobin levels were determined by adherence to blood supplement consumption, practices related to blood supplement tablets and consumption of Fe sources (adjusted model R2 is 0.253, F 11.8, Sig 0.000). This explains 25.3% of the relationship between several determinant factors of anemia and hemoglobin levels in the study respondents.